Intervensi Relaksasi Otot Progresif (Progressive Muscle Relaxation) pada Pasien Kanker yang Mengalami Fatigue - Dwi Suryani; Tuti Nuraini; Dewi Gayatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of progressive muscle relaxation (PMR) on fatigue in cancer patients. The method used is a systematic review. The results showed that of the 7 articles reviewed, 6 showed that PMR could reduce fatigue or fatigue in cancer patients and 1 article showed no significant difference in applying progressive muscle relaxation to fatigue or fatigue. In conclusion, PMR can reduce the fatigue experienced by cancer patients. Keywords: Cancer, Fatigue, Progressive Muscle Relaxation